Petrography and geochemistry of sandstones from the middle Jurassic Zhiluo Formation in the northern margin, Ordos Basin: implications for provenance, tectonic setting, paleoweathering, paleoclimate, and sandstone-type uranium mineralization - Luo, Xiaoneng; Peng, Suping; Li, Ziying; He, Feng; Li, Xide; Zhang, Zilong (Frontiers in Earth Science, 2025)
This study aims to analyze the provenance of Middle Jurassic Zhiluo Formation sandstones exposed by drilling in the northern Ordos Basin (Bayingqinggeli area) and reconstruct the tectonic setting, paleoclimate, and paleoweathering conditions of their source rocks through integrated petrographic and geochemical analyses (major, trace, and rare earth elements). Comprehensive evaluation of mineral assemblages and geochemical signatures reveals that the detrital components of the studied sandstones were predominantly derived from multiple recycled felsic (granitic) igneous sources, with subordinate contributions from intermediate igneous (granodioritic), metamorphic (gneissic), and mafic igneous (andesitic) provenances. Diagnostic elemental ratios including La/Sc, Th/Sc, and Co/Th demonstrate a principal derivation from felsic lithologies (granites and gneisses) coupled with recycled quartzose sedimentary sources. Chondritenormalized REE patterns exhibit light REE (LREE) enrichment, flat heavy REE (HREE) distributions, and pronounced negative Eu/Eu* anomalies, showing close affinity to Upper Continental Crust (UCC) characteristics dominated by felsic lithologies. Geochemical proxies and trace element ratios (e.g., Th/U, Th/Sc) indicate that the source area underwent moderate to intense chemical weathering, primarily under arid climatic conditions with intermittent episodes of warm, semi-humid to humid paleoenvironments. The integrated dataset further suggests a complex exhumation history involving cratonic basement uplift and reactivation of Paleozoic orogenic belts during the Mesozoic era.